Notes on the Peruvian wart - Carrión, Daniel Alcides (1998)
Wart blood -. Collectible Wart -. Wart andicola (Dr. Salazar) -. Wart of Castile, zapo or quinoa -. Bottlenose Wart. The wart is an anemic irregular pyrexia, endemic and non-contagious form; characterized mainly be accompanied by pain and muscle contractions (cramps); arthralgia infarction and more or less intense ostalgias; produces a polymorphic eruption; has but variable cyclical pattern, generally long duration, which is not influenced by the treatment; is also susceptible to numerous complications.